Resor Pemandian Air Panas Di Desa Pawan Rokan Hulu Dengan Pendekatan Arsitektur Hijau - Izazul Lizar; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Rokan Hulu regency has so many attractions, including the nature attractions and the religion attractions. One of the nature attractions in Rokan Hulu is the hot spring in Pawan village. But, the condition is so concern because its not maintained well by the society and government. Therefore, the hot spring in Pawan village has re-designed with the new concept to increased the tourism destinations in Riau province, especially in Rokan Hulu. The Hotspring Resort is good alternative object for the hot spring in Pawan village, with tje natural view that support to the resort. One of them, Bukit Suligi, Bukit Barisan view. The design of the Hotspring Resort is forwading the green architecture principle. The aim is to design the building that minimalize negative effect to the environment, nature and human being. So that will build up the better and healthier place. Moreover, the concept of the design is